2018
DOI: 10.1038/s41598-018-32662-1
|View full text |Cite
|
Sign up to set email alerts
|

Impedance Spectroscopy as a Novel Approach to Probe the Phase Transition and Microstructures Existing in CS:PEO Based Blend Electrolytes

Abstract: In this work the role of phase transition of PEO from crystalline to amorphous phases on DC conductivity enhancement in chitosan-based polymer electrolyte was discussed. Silver ion-conducting polymer electrolytes based on chitosan (CS) incorporated with silver nitrate (AgNt) is prepared via solution cast technique. Various amounts of polyethylene oxide (PEO) are added to the CS:AgNt system to prepare blend polymer electrolytes. Ultraviolet-visible (UV-vis) spectrophotometry is used to confirm that the blended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 62 publications
2
30
0
1
Order By: Relevance
“…Recently, the use of biopolymer materials has raised special attention as they are abundant in nature and are eco-friendlier. Several polymers have been found to be suitable as a polymer host, including chitosan 16 , 17 , cellulose 2 , 18 , 19 , agarose 20 , and carboxymethyl cellulose (CMC) 21 26 . Of these, CMC shows a good potential to act as a polymer host for proton-conducting biopolymer electrolytes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the use of biopolymer materials has raised special attention as they are abundant in nature and are eco-friendlier. Several polymers have been found to be suitable as a polymer host, including chitosan 16 , 17 , cellulose 2 , 18 , 19 , agarose 20 , and carboxymethyl cellulose (CMC) 21 26 . Of these, CMC shows a good potential to act as a polymer host for proton-conducting biopolymer electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…The enhancement of polymer properties through polymer blending or copolymers 13 , 16 , 17 , 23 25 , 28 , plasticization 22 , 29 and composite formation 3 , 12 have been competitively considered in the research community. The polymer blend technique was applied in the present study due to its low cost and easy processing as well as its ability to provide promising conductivity values.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the manufacture of membranes and membrane electrodes, 1.0 mg of enzyme was used in 0.0350 g of PVA. According to (Aziz et al, 2018) that the mixed samples showed the highest peak absorbance peak, the absorbance was analyzed by UV-Vis in the range of 180-1000 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Besarnya konduktivitas ini ditentukan oleh jumlah konsentrasi elektrolit. Energi listrik dapat ditransfer melalui materi berupa hantaran yang bermuatan listrik yang berwujud arus listrik yang berarti bahwa harus ada pembawa muatan listrik di dalam materi serta adanya gaya yang menggerakkan pembawa muatan tersebut (227)(228)(229)(230)(231) . Pembawa muatan dapat berupa elektron atau dapat juga digunakan ion positif dan ion negatif dalam larutan elektrolit dan leburan garam (232) .…”
Section: Konduktivitasunclassified